A Summary of the Existing Data on Cleft Surgical Outcomes: What Do We Not Know? - Priyanka Naidu, MBChB, MS; Alexander T. Plonkowski, MBBS, MRes; Caroline A. Yao, MD, MS; William P. Magee, III, MD, DDS (Plastic and Reconstructive Surgery, Global Open)
Summary:. Globally, cleft surgical protocols have nuanced differences between centers, yet the goals of cleft lip and palate (CLP) repair are similar. These protocols all aim to achieve optimal aesthetic appearance and speech outcomes while limiting significant complications such as velopharyngeal insufficiency and midface hypoplasia. Variability in complication rates following primary CLP repair has been well documented within the literature. A series of systematic reviews investigate the impact of factors on surgical outcomes, all demonstrating an inability to comment on the ideal technique and timing to optimize outcomes. This article presents a summary of the current state of the literature on surgical outcomes following CLP repair. Studies were limited by small samples sizes; standardized measurement tools; study design; and lack of diversity in cleft phenotype, severity, and patient population. These limitations highlight the need for further research with more representative populations globally, standardized measurement tools, and a global consortium of cleft surgeons to make recommendations based on improved data. As the need for training in cleft surgery expands across the globe, evidence-based algorithms are essential to optimize outcomes and limit costly complications.